Women's awareness regarding the use of dental imaging during pregnancy - Lina Bahanan; Abdulrahman Tehsin; Reyouf Mousa; Mohammed Albadi; Mohammed Barayan; Emad Khan; Hanadi Khalifah (BMC, 2021)
Abstract Background There is often anxiety among pregnant women about dental imaging during pregnancy. This may hinder some women from seeking dental treatment during pregnancy and consequently, may negatively affect the oral health of the mother and fetus. This study was conducted to assess women's awareness regarding the use of dental imaging during pregnancy. Methods In this cross-sectional study, the electronic distribution of structured questionnaires was done via social media. The self-administered questionnaires contained questions related to women's knowledge regarding the radiation protection measures during dental imaging, the safest period for dental imaging, the type of radiographs that can be acquired during pregnancy, and the possibility of radiation-induced malignancy and fetal malformation as a result of dental imaging. Results In total, 410 completed questionnaires were received and analyzed. More than half of the participants were 30-49 years of age. The majority of the participants (91%) demonstrated poor knowledge concerning dental imaging. Only 4% reported that pregnant women can have dental imaging during any trimester. The majority believed that panoramic images and cone-beam computed tomography should not be acquired during pregnancy. The majority also believed there is a high risk of congenital malformation due to dental imaging and were unsure about the oncogenic risks. Conclusions Our study suggests that there is insufficient knowledge about dental imaging safety during pregnancy. This misconception may have a direct impact on the attitude toward seeking dental care. Therefore, community awareness initiatives aimed at informing our society about radiation exposure, safety, and required protection measures are critical.